2016
DOI: 10.3390/nu8090545
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Dietary Patterns, ADRβ2 Gln27Glu and ADRβ3 Trp64Arg with Regard to Serum Triglyceride Levels: J-MICC Study

Abstract: Interactions between dietary patterns and 2 β-adrenergic receptor (ADRβ) gene polymorphisms (ADRβ2 Gln27Glu and ADRβ3 Trp64Arg) were examined with regard to the effects on serum triglyceride levels. The cross-sectional study comprised 1720 men and women (aged 35–69 years) enrolled in the Japan Multi-Institutional Collaborative Cohort (J-MICC) Study. Genotyping was conducted using a multiplex polymerase chain reaction-based invader assay. We used 46 items from a validated short food frequency questionnaire and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
(77 reference statements)
0
3
0
Order By: Relevance
“…The average intake of 46 foods over the past year was assessed with a validated short food frequency questionnaire (FFQ), as described in previous reports [20][21][22][23]. For daily amounts of three staple foods (rice, bread, and noodles), questions were asked about the portion/serving size and frequency of consumption (six categories: almost none, 1-3 times/month, 1-2 times/week, 3-4 times/week, 5-6 times/week, and daily).…”
Section: Dietary Assessmentmentioning
confidence: 99%
“…The average intake of 46 foods over the past year was assessed with a validated short food frequency questionnaire (FFQ), as described in previous reports [20][21][22][23]. For daily amounts of three staple foods (rice, bread, and noodles), questions were asked about the portion/serving size and frequency of consumption (six categories: almost none, 1-3 times/month, 1-2 times/week, 3-4 times/week, 5-6 times/week, and daily).…”
Section: Dietary Assessmentmentioning
confidence: 99%
“…However, the dietary pattern approach is preferred, especially in nutritional epidemiologic studies [ 4 ]. Similar studies have also used the dietary pattern approach in gene-diet interaction studies [ 5 , 6 ]. In addition, significant gene-diet interactions were also observed in our previous study [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Seafood was determined to be the major contributor to the arsenic level among the diets separated into six categories, in accordance with a previous study. 59 Our analysis using the pseudo- R 2 test revealed that the contribution of seafood to arsenic level was the largest (>25%) among all confounders. Further analysis of seafood classified into eight items indicated a positive association between arsenic level in fasting serum and ingestion frequencies of fish meat, bone-edible small fish, seaweed, and squid/octopus/shrimp/crab.…”
Section: Discussionmentioning
confidence: 75%